Current-carrying and electrostatic plasma-electron lenses controlled by the external programmed magnetic field - Ivanov, B.I.; Butenko, V.I. (Вопросы атомной науки и техники, 2000)
In this work the studies of long uniform, and non-uniform modified adiabatic plasma lenses of different types are performed that intended for middle and high energy ion beam focusing.